2020
DOI: 10.3390/su12030756
|View full text |Cite
|
Sign up to set email alerts
|

Proximal Cities: Does Walkability Drive Informal Settlements?

Abstract: The uncontrolled growth of urban areas worldwide is pushing a substantial part of the urban population to the fringes of society, confining them to the unsecure and unhygienic settlements that we call “informal.” These settlements lack in intelligible layout and essential services and infrastructures, thus representing a challenging issue for policy makers and urban designers in the development of renewal programs and strategies. In order to support the facing of these issues through an on-site upgrade approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…This is not a solution but a way to compare model results with the perception of real people living in the area. The use of SSA as robust analytic for the evaluation of mobility issue in urban regeneration participatory practice presents a wide range of applications connected with the increasing importance that regeneration plays in urban development [85,86]. The evidence from CAST project allows one to affirm that SSA contributed to the cognitive participatory framework in terms of sharing useful quantitative measures facilitating comparisons among different scenarios connected with urban mobility.…”
Section: Discussionmentioning
confidence: 99%
“…This is not a solution but a way to compare model results with the perception of real people living in the area. The use of SSA as robust analytic for the evaluation of mobility issue in urban regeneration participatory practice presents a wide range of applications connected with the increasing importance that regeneration plays in urban development [85,86]. The evidence from CAST project allows one to affirm that SSA contributed to the cognitive participatory framework in terms of sharing useful quantitative measures facilitating comparisons among different scenarios connected with urban mobility.…”
Section: Discussionmentioning
confidence: 99%
“…Although most of these settlements are often associated with negative characteristics and precarious living conditions [58], recent research has shown that these intense urban environments reflect the needs and requirements of their dynamic communities [20]. The search for solutions to urban and social issues prompted by informal settlements is one of the main challenges in contemporary urban planning, and a comprehensive study of their mechanism, including the autopoietic, self-organization, and self-determination principle, can promote the idea of a more resilient society.…”
Section: Urban Autopoiesis and Informal Settlementsmentioning
confidence: 99%
“…According to Cutini et al [20], the Informal Society, which rules informal communities, is constituted by a physical and a social level. The development of informal settlements depends on the interaction between these two levels, and by analyzing their relationship from the configurational point of view [21,22], recent studies have shown that it is possible to observe the autopoietic urban dynamics in the evolution of their topo-geometrical urban structure [19,23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The population of the area grew from around 6700 in 1990 to at least 60,000 at present (PSA 2016; PhilAtlas 2020). This population growth is partly explained by development programs the city aimed at the area (Cutini et al 2020). While BASECO has formal residents, the area near the shoreline, which is the focus of this study, is defined by informal settlements that are characterized by the irregular spatial arrangement of the houses and residents without land titles (Navarra 2016).…”
Section: The Bataan Shipping and Engineeringmentioning
confidence: 99%